Effects of short compression pants on aerobic energy cost and subjective sensation responses during submaximal running exercise - Bringard, A.; Perrey, S.; Belluye, N. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The effects of compressive pants on athletic performance have been mainly evaluated during power sports (Kraemer et al., 1996). Based on lower body kinematics and jump performance, the authors suggested that particular compressive pants may improve short, explosive types of athletic performance. Yet the data are limited as to whether such pants have any influence on physical performance and perceived exertion during endurance sports such as running. The purpose of this study was to evaluate the effect of short compression pants on energy expenditure per unit of distance, that is the energy cost (EC) at various submaximal intensity. In this way, Moritani (2002) reported that oxygen consumption (VO2) and muscle activity tend to decrease during submaximal intensity in cycling by wearing long compression pants compared to control garments. We hypothesised therefore that short compression pants will influence the energy cost in a group of trained middle-distance runners. Aerobic EC is considered as a critical element of overall success in running and skiing performance (Millet et al., 2002). Methods Six male trained runners [(mean ± SD) age 31 ± 1 yrs; body mass 66 ± 8 kg; height 177 ± 6 cm) volunteered to participate in the study. They performed on an indoor 200-m track during three different days a graded exercise test (initial speed set at 10 km/h with increments of 2 km/h every 3 min) until maximal VO2 achievement. During testing session subjects wore either short compression pant (Decathlon®), short elastic pant, or conventional short in a random order. Pulmonary gas exchanges and heart rate were recorded continuously during all testing session with a portable system (K4b2, Cosmed, Italy).VO2 were smoothed over 5 breaths and averaged over the last 15 s of each 3 min step. Net energy cost (ml/kg/m) was then calculated for the following running speeds: 10, 12, 14 and 16 km/h. Subject perceptions of thermal comfort, exertion and sweating sensations were obtained after each testing session. Body mass loss was calculated as the difference in pre- and post- exercise body weight by way of bioelectrical impedance balance (Tanita BF-350, UK). A repeated-measures ANOVA test was performed between the conditions and significance was set at P<0.05. Results There were no differences in thermal stress (~ 31 °C), in body mass loss, and in thermal comfort, sweating and exertion sensations between clothing. At 12 km/h, there was a significant effect among the three clothing [F(2,5) = 4.61, P<0.05]. EC was significantly higher by wearing short (Fig. 1) compared to Decathlon® and elastic pants. Note that there was the same trend at 10 and 14 km/h (P>0.05). There was no difference in heart rate and maximal VO2 between clothing. These preliminary results demonstrate that in the same environmental conditions (31° C, no wind) a better running economy may be obtained at submaximal exercise intensity (from 10 to 14 km/h) by wearing Decathlon® and elastic pants compared to conventional short. Wearing compression pant during running exercise may enhance overall circulation to promote a lower energy expenditure at a given submaximal speed, but further work is needed to understand the mechanisms of this ergonomic interface during submaximal and prolonged running exercise.